Analysis of Vaccine Hoax Information in Facing the Covid-19 Crisis on Twitter - Muh. Syaiful; Muh. Akbar; Tuti Bahfiarti (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Present the new media (internet) as a new challenged in the world of information, especially on hoax information. The increase in hoax messages has also been a challenge in managing the Covid-19 crisis, with social media becoming the new venue for the spread of hoax messages. The objective of the research was to analyze information on the Covid-19 vaccine on Twitter to be more careful in choosing and to reveal the disseminating information. This research used qualitative content analysis methods according to Philip Mayring and utilized the search engine on Twitter to collect data within a certain time span. The result of this research, found some hoax information on Twitter such as: Sinovac vaccine was haram, vaccine was killed, vaccine was spayed, and vaccines changed human DNA.